EFFECTS OF FOLIAR APPLICATION OF AMINOPLASMAL, BORON, ZINC AND THEIR INTERACTIONS ON FRUIT SET AND YIELD CHARACTERISTICS OF PISTACHIO (Pistacia vera L) cv. HALABY - & Tayib, Ibrahim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was performed at a private orchard in the Ekmale area of Duhok Governorate, Kurdistan Region, Iraq, during the seasons of 2016 and 2017 to investigate the effects of foliar sprays of three concentrations of aminoplasmal (0, 100, 200 ml.L−1), three concentrations of boron (0, 200, 300 mg. L−1) and three concentrations of zinc (0, 400, 600 mg. L−1) on fruit set and yield characteristics of 14-years old "Halaby" pistachio. The factorial experiment within randomized complete block design was used. Foliar spraying of studied elements was applied at twice during growing seasons. The results showed that fruit set percentage, yield, and yield characteristics were significantly affected by foliar application of aminoplasmal, Boron and Zinc each alone. In combination, the triple interactions among 200ml.L-1 aminoplasmal plus 300mg.L-1 boron and 600mg.L-1 zinc was the most affected one which surpassed significantly on the control treatment and other treatments at both seasons. This data also display that primary fruit set% and final fruit set% in 2016 were higher than that of 2017, but yield, carbohydrate % and fat % were greater in the 2017 than they were in the 2016. In general, in this study, it was discovered that treatments with aminoplasmal, boron and zinc significantly increased yield of pistachio.